Konstruksi Teori dalam Penelitian Kualitatif: Pendekatan, Metodologi, dan Kontribusi terhadap Ilmu Sosial - Sa’diyah, Halimatus; Rafiuddin, Moh. (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Qualitative research plays a crucial role in the advancement of knowledge, particularly in understanding research methodologies and the theories applied within qualitative studies. The emergence of qualitative research methodology is a response to traditions that emphasize cultural studies and interpretation. In qualitative research, theory must be capable of uncovering social realities and exploring the meaning behind various social phenomena. Theory construction in qualitative research not only aims to provide an in-depth understanding of social phenomena but also seeks to build new perspectives that enrich social science studies. This approach requires a strong grasp of academic disciplines and social realities analyzed through methodological rigor. Thus, theory in qualitative research has remained dominant from the past to the present, contributing significantly to the development of research methodologies and a more comprehensive understanding of social life.